Pelatihan Penggunaan Aplikasi Mendeley Dalam Penyusunan Tugas Akhir Bagi Mahasiswa Farmasi Universitas Megarezky - Andi Meinar Dwi Rantisari; Vivit Rosmayanti; Sriwahyuni Sriwahyuni; Muliaty Ibrahim; Sukmawati Sukmawati; Adriandy Saleh (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Writing scientific papers is one of the obligations of students as a condition for completing studies. However, in their preparation, students are often trapped in unintentional acts of plagiarism, namely copying and pasting a written work without putting in the source. Therefore, the existence of a software that functions as a